2021
DOI: 10.37992/2021.1203.098
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characterization and assessment of genetic diversity in pigeonpea [Cajanus cajan (L.) Millsp.] germplasm

Abstract: A total of 243 genotypes of pigeonpea were evaluated during Kharif, 2019 on the basis of DUS and D 2 -cluster analysis. Pigeonpea genotypes were grown in the augmented design for evaluation. Morphological characterization was done based on plant descriptors for pigeonpea at different stages of plant growth. The cluster analysis grouped all the genotypes into six clusters. The clusters I, II, III, IV, V and VI had 32,3,9,79,115 and 5 genotypes, respectively. The inter cluster distance was maximum between cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…4). Chaudhary et al (2021), Rupika and Bapu (2014) and Yohane et al (2020) also reported yellow flower colour as prominent in pigeonpea. With regard to the number of seeds per pod, three seeds per pod were observed in 17 genotypes (30.91 %) and 38 genotypes (69.09 %) had four seeds per pod.…”
Section: Resultsmentioning
confidence: 91%
“…4). Chaudhary et al (2021), Rupika and Bapu (2014) and Yohane et al (2020) also reported yellow flower colour as prominent in pigeonpea. With regard to the number of seeds per pod, three seeds per pod were observed in 17 genotypes (30.91 %) and 38 genotypes (69.09 %) had four seeds per pod.…”
Section: Resultsmentioning
confidence: 91%
“…Pod pubescence was present in all 70 genotypes. Sivabharathi et al, Chaudhary et al(2021) also reported the presence of pod pubescence in all 236 pigeonpea genotypes. Small seeds were found in 30 genotypes and weighed less than 10 g per 100 seeds, medium seeds were found in 39 genotypes and weighed 10.1 g to 13.0 g, and large seeds were found in one genotype and weighed 14.12 g (i.e., >13.0 g) viz., MACS 1254.…”
Section: Dark Green Greenmentioning
confidence: 92%